Speed training for team sport athletes - Faccioni, A.
1. Speed demands of team athletes (acceleration, agility) 2. Physiology behind increase in acceleration and agility (Increase in speed strength) 3. Technique requirements to maximise acceleration 4. Drills to improve acceleration 5. Development of specific: speed endurance. 6. Planning into yearly program